Determining Factors of Dividend Policy In Basic and Chemical Industry - Khairunisa Khairunisa; Warsono Warsono; Novita Ratna Satiti (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine the determinants of dividend policy in basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The number of samples in this study was 13 companies with a purposive sampling method. Data collection is carried out by means of documentation techniques, namely through the company's annual report. The results of this study indicate that liquidity has a significant and negative effect on dividend policy, profitability has a negative and significant effect on dividend policy, and profitability is the variable that has the greatest effect on dividend policy.